CD47 is required for mesenchymal progenitor proliferation and fracture repair - Robert L. Zondervan; Christina A. Capobianco; Daniel C. Jenkins; John D. Reicha; Livia Fredrick; Charles Lam; Jeanna T. Schmanski; Jeffery S. Isenberg; Jaimo Ahn; Ralph S. Marcucio; Kurt D. Hankenson (Bone Research)
Abstract CD47 is a ubiquitous and pleiotropic cell-surface receptor. Disrupting CD47 enhances injury repair in various tissues but the role of CD47 has not been studied in bone injuries. In a murine closed-fracture model, CD47-null mice showed decreased callus bone formation as assessed by microcomputed tomography 10 days post-fracture and increased fibrous volume as determined by histology. To understand the cellular basis for this phenotype, mesenchymal progenitors (MSC) were harvested from bone marrow. CD47-null MSC showed decreased large fibroblast colony formation (CFU-F), significantly less proliferation, and fewer cells in S-phase, although osteoblast differentiation was unaffected. However, consistent with prior research, CD47-null endothelial cells showed increased proliferation relative to WT cells. Similarly, in a murine ischemic fracture model, CD47-null mice showed reduced fracture callus size due to a reduction in bone relative to WT 15 days-post fracture. Consistent with our in vitro results, in vivo EdU labeling showed decreased cell proliferation in the callus of CD47-null mice, while staining for CD31 and endomucin demonstrated increased endothelial cell density. Finally, WT mice with ischemic fracture that were administered a CD47 morpholino, which blocks CD47 protein production, showed a callus phenotype similar to that of ischemic fractures in CD47-null mice, suggesting the phenotype was not due to developmental changes in the knockout mice. Thus, inhibition of CD47 during bone healing reduces both non-ischemic and ischemic fracture healing, in part, by decreasing MSC proliferation. Furthermore, the increase in endothelial cell proliferation and early blood vessel density caused by CD47 disruption is not sufficient to overcome MSC dysfunction.